The Role of Teacher Followership Mediation For Authentic Leadership Toward Teacher Work Engagement - Herdian, Herdian; Haenilah, Een Yayah; Hariri, Hasan (FKIP Universitas Lampung, 2023)
The Role of Teacher Followership Mediation for Authentic Leadership toward Teacher Work Engagement. Objectives: This research aimed to investigate how authentic leadership affects teacher followership and teacher work engagement mediated by teacher followership. Methods: A quantitative survey was employed. The population was civil servant teachers of senior high and vocational schools from 15 districts of Lampung Province, with a sample of 378 teachers randomly selected and completed the questionnaires distributed through google form The gathered data were analyzed using SEM Amos Version 23. Findings: Authentic leadership influenced teacher followership, teacher followership influenced teacher work engagement, and teacher followership mediated the influence of authentic leadership on teacher work engagement. Conclusion: Authentic leadership positively and significantly inluences teacher work engagement mediated by teacher followership. Keywords: authentic leadership, teacher followership, teacher work engagement, role of mediationDOI: http://dx.doi.org/10.23960/jpp.v13.i3.202322